CSF monoamine metabolites, cholinesterases and lactate in the adult hydrocephalus syndrome (normal pressure hydrocephalus) related to CSF hydrodynamic parameters. Issue 3 (March 1991) - Malm, J; Kristensen, B; Ekstedt, J; Adolfsson, R; Wester, P
Abstract : Monoamine metabolites, cholinesterases and lactic acid in lumbar cerebrospinal fluid (CSF) were investigated on patients with the adult hydrocephalus syndrome (idiopathic normal pressure syndrome; AHS, n = 15), Alzheimer's disease (AD, n = 14), multi-infarct dementia (MID, n = 13) and controls (n = 21). Patients had clinical and CSF hydrodynamic investigations. Monoamine concentrations were determined by reversed-phase liquid chromatography, cholinesterases and lactate were determined photometrically. In the AHS patients, CSF monoamine concentrations were not significantly different compared with controls, AD or MID patients. AHS and AD patients showed a similar reduction of CSF acetylcholinesterase activity compared with controls. Positive correlations were found in concentrations of CSF homovanillic acid, CSF 5-hydroxyindoleacetic acid and CSF lactic acid versus CSF outflow conductance (that is, resistance against CSF outflow) in the AHS patients. A similar pattern was observed in a subgroup of MID patients characterised by dilated ventricles and disturbed CSF hydrodynamics. These data suggest that a low CSF outflow conductance may facilitate the clearance of acidic substances from the arachnoid space at the probenecid sensitive active transport site. Alternative explanations would be that a pathologically low CSF outflow conductance is accompanied by an inverse caudorostral flow of CSF or a compromised trans-ependymal diffusion.